Serotonin and dopamine receptors in motivational and cognitive disturbances of schizophrenia - Sumiyoshi, Tomiki; Kunugi, Hiroshi; Nakagome, Kazuyuki (Frontiers in Neuroscience, 2014)
Negative symptoms (e.g. decreased spontaneity, social withdrawal, blunt affect) and disturbances of cognitive function (e.g. several types of memory, attention, processing speed, executive function, fluency) provide a major determinant of long-term outcome in patients with schizophrenia. Specifically, motivation deficits, a type of negative symptoms, have been attracting interest as a moderator of cognitive performance in schizophrenia and related disorders, and also a modulating factor of cognitive enhancers/remediation. These considerations suggest the need to clarify neurobiological substrates regulating motivation. Genetic studies indicate a role for the monoamine systems in motivation and key cognitive domains. For example, polymorphism of genes encoding catecholamine-O-methyltransferase, an enzyme catabolizing dopamine (DA), affects performance on tests of working memory and executive function in a phenotype (schizophrenia vs. healthy controls)-dependent fashion. On the other hand, motivation to maximize rewards has been shown to be influenced by other DA-related genes, such as DARPP-32 and DA-D2 receptors. Serotonin (5-HT) receptors may also play a key role in cognitive and motivational disabilities in psychoses and mood disorders. For example, mutant mice over-expressing D2 receptors in the striatum, an animal model of schizophrenia, exhibit both decreased willingness to work for reward and up-regulation of 5-HT2C receptors. Taken together, genetic predisposition related to 5-HT receptors may mediate the diversity of incentive motivation that is impaired in patients receiving biological and/or psychosocial treatments. Taken together, research into genetic and neurobiological measures of motivation, in association with 5-HT receptors, is likely to facilitate intervention into patients seeking better social consequences.